Flerspråkighet i ett globaliserat samhälle: uppfattningar om minoritetsspråket som framtidsresurs (Sociologisk Forskning, 2011)
Multilingualism in a globalized society: The minority language as a future resourceIn this article the author investigates how the globalization of society is used as a reference in the discussion of future opportunities among minority language speaking youths in Sweden. A spatial typology of four different types of societies are constructed, the national, the multicultural, the diasporic and the transnational society, all giving the expression of different levels of globalization. These are used as layers of reference put upon the empirical data, functioning as a raster on a screen. The result is a pattern of expressions in three societal dimensions, the economic, the social and the cultural dimension. The findings of the investigation show that the minority language as a future resource of opportunities is anchored in all four societal types and in all three dimensions. In the empirical data (the youths interviewed) the ability of anchoring (finding stories, opportunities etc.) is less frequent when it comes to the diasporic and the transnational as a foundation for opportunity and more frequent when it comes to the national and the multicultural.
Keywords: transnationalism; diaspora; multiculturalism; nationalism and language.